Incidence of Extrusion Following Type I Polypropylene Mesh “Kit” Repairs in the Correction of Pelvic Organ Prolapse - James C. Lukban; Roger D. Beyer; Robert D. Moore (Obstetrics and Gynecology International)
Introduction and Hypothesis. We sought to determine the mesh extrusion (vaginal exposure) rates and subject outcomes following IntePro (Type I polypropylene) mesh “kit” repairs for vaginal prolapse. Methods. Data were pooled from two prospective multicenter studies evaluating the safety and efficacy of the Perigee and Apogee (American Medical Systems, Minnetonka, Minn, USA) to treat anterior and posterior/apical prolapses, respectively. Extrusions involving the anterior compartment (AC) or posterior compartment/apex (PC/A) were recorded. Results. Two hundred sixty women underwent mesh placement, with a total of 368 mesh units inserted (173 in the AC and 195 in the PC/A). Extrusions were noted in 13 (7.5%) of AC implants and 27 (13.8%) of PC/A implants through 12 months. No difference was seen between those with and without extrusion in regard to anatomic cure, postoperative painor quality of life at 1 year. Conclusions. Extrusion had no apparent effect on short-term outcomes. Given the unknown long-term sequellae of vaginal mesh exposure, a thorough assessment of risks and benefits of transvaginal mesh placement should be considered at the time of preoperative planning.